Health promotion interventions for African Americans delivered in U.S. barbershops and hair salons- a systematic review - Kelly N. B. Palmer; Patrick S. Rivers; Forest L. Melton; D. Jean McClelland; Jennifer Hatcher; David G. Marrero; Cynthia A. Thomson; David O. Garcia (BMC, 2021)
Abstract Background African American adults suffer disproportionately from obesity-related chronic diseases, particularly at younger ages. In order to close the gap in these health disparities, efforts to develop and test culturally appropriate interventions are critical. Methods A PRISMA-guided systematic review was conducted to identify and critically evaluate health promotion interventions for African Americans delivered in barbershops and hair salons. Subject headings and keywords used to search for synonyms of 'barbershops,' 'hair salons,' and 'African Americans' identified all relevant articles (from inception onwards) from six databases: Academic Search Ultimate, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Embase, PsycINFO, PubMed, Web of Science (Science Citation Index and Social Sciences Citation Index). Experimental and quasi-experimental studies for adult (> 18 years) African Americans delivered in barbershops and hair salons that evaluated interventions focused on risk reduction/management of obesity-related chronic disease: cardiovascular disease, cancer, and type 2 diabetes were included. Analyses were conducted in 2020. Results Fourteen studies met criteria for inclusion. Ten studies hosted interventions in a barbershop setting while four took place in hair salons. There was substantial variability among interventions and outcomes with cancer the most commonly studied disease state (n = 7; 50%), followed by hypertension (n = 5; 35.7%). Most reported outcomes were focused on behavior change (n = 10) with only four studies reporting clinical outcomes. Conclusions Health promotion interventions delivered in barbershops/hair salons show promise for meeting cancer screening recommendations and managing hypertension in African Americans. More studies are needed that focus on diabetes and obesity and utilize the hair salon as a site for intervention delivery. Trial registration PROSPERO CRD42020159050 .